Tax Planning , Risk Reputation , and Discipline Managerial : Overview Literature on Companies with Different Life Cycles - Hollines Luahambowo; Yessica Amelia (LPPM STIE Kasih Bangsa, 2024)
This literature review explores the impact of tax planning on reputational risk and managerial discipline across different stages of a firm's life cycle. The findings indicate that aggressive tax planning offers significant benefits during the introduction and growth stages by providing cash resources for investment and expansion. However, in the maturity and decline stages, such strategies can lead to reputational risks and weaken managerial discipline. The study highlights the moderating role of corporate governance structures, such as board diversity, in mitigating these negative effects by enhancing oversight and decision-making. Managers are advised to align tax planning strategies with the firm's life cycle stage to maximize benefits and minimize long-term risks. Despite offering valuable insights, this study is limited by its qualitative nature and reliance on existing literature, necessitating further empirical research.